Scientific Comparison of Different Online Heart Rate Monitoring Systems - Martin Schönfelder; Georg Hinterseher; Philipp Peter; Peter Spitzenpfeil (International Journal of Telemedicine and Applications)
Recent technical development focused on real-time heart rate monitoring instead of postexercise evaluation of recorded data. There are several systems on the market that allow direct and real-time monitoring of several individuals at the same time. The present study compared the systems of Polar, Acentas, Activio, and Suunto in a field test with twelve subjects regarding failure quota, operating distance, and ECG validity. Moreover, the installation and use of software and hardware were evaluated with a quality rating system. Chest belts were evaluated with a questionnaire, too. Overall the system of Acentas reached the best mark of all systems, but detailed results showed that every system has its advantages and disadvantages depending on using purpose, location, and weather. So this evaluation cannot recommend a single system but rather shows strength and weakness of all systems and additionally can be used for further system improvements.